A case with a novel GATA1 variant mimicking immune thrombocytopenia attacks - Elif Habibe Aktekin; Serdar Ceylaner; Şeyda Beşen; Ayşe Erbay; Nalan Yazıcı (Platelets)
One of the leading thrombocytopenia occasions in childhood is immune thrombocytopenia (ITP). Small number of these patients do not respond to treatment methods known to be effective for ITP such as corticosteroids, intravenous immunoglobulin and thrombopoietin receptor agonists (eltrombopag, romiplostim, etc.) and have serious bleeding symptoms. We present a case in which a molecular genetic analysis was performed due to challenging responses to medical treatment for severe systemic bleeding symptoms which were similar to ITP. A hemizygous variant was detected in the GATA1 gene and a homozygous variant in the ATP2A1 gene for Brody myopathy. Eltrombopag, romiplostim, IVIG and corticosteroid were applied to resistant thrombocytopenia of the patient without knowing the cause. Patient had response in platelet counts in some occasions. This situation attracted our attention after the detection of this GATA variant in the etiopathogenesis of thrombocytopenia. Further investigations should be performed for much more rare causes of thrombocytopenia in patients with refractory thrombocytopenia attacks.